Beberapa Faktor Host yang Berpengaruh terhadap Kejadian Gonore pada Wanita Pekerja Seks Tidak Langsung (Studi pada Pemandu Lagu Karaoke di Kabupaten Wonosobo) - Anita Nugrahaeni; Muchlis Achsan Udji Sofro; Zahroh Shaluhiyah; Antono Suryosaputro; Bagoes Widjanarko (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background : Gonorrhoea is a health problem with increasing rates worldwide. The phenomena of increasing and spreading gonorrhoea cases affect the high risk groups including Indirect Female Sex Workers (IFSWs). The aim of this study was to explain some host factors as the risk factors of gonorrhoea in IFSWs in Wonosobo.Methods : This is an observational research with control case design. The study population was IFSWs who worked as lady companions in karaoke under the guidance of NGO Wonosobo Youth Center and had done the STI examination by STI clinic. The subjects were 84 consist of 42 case and 42 control. Samples were collected by consecutive sampling technique. Data analysis used chi-square, Odd Ratio (OR) and logistic regression.Results : Influencing factors to the occurence of gonorrhoea in IFSWs were history ofcombination sexual activity (p=0,013; OR=3,843; 95% CI= 1,323-11,63), history of STI (p=0,013; OR=3,863; 95% CI= 1,328-11,240), and consistency of condom use (p=0,009; OR=5,778; 95% CI=1,553-21,491).Conclusion : Factors that had been proven to influence the occurence of gonorrhoea in ISFWs were history of combination sexual activity, history of STI, and consistency of condom use.